Formula of deception - Parks, Carrie Stuart (Thomas Nelson, 2018)
"An escaped killer uncovers one of World War II's most dangerous secrets--a secret that desperate men will do anything to keep. After the murder of her twin sister, Murphy Anderson changed her name and appearance and moved to Kodiak, Alaska, to avoid the press and publicity. But when local authorities discover she's an artist and request her help in drawing a dying man's memories, she unintentionally ends up in the limelight again--and may be back in the killer's crosshairs. The deathbed confessions of an Alaskan hunter has Murphy drawing five bodies discovered on remote Ruuwaq Island ten years ago. But what investigators discover there has them mystified. Evidence suggests that the bodies may have been deliberately destroyed, and what they uncover in an abandoned World War II Quonset hut only brings more questions. As one by one the people who were at the hut die, Murphy knows there is something much deeper at stake. What happened there during WWII? And who is willing to kill to keep those secrets buried?"--